MONOFTONGISASI DIFTONG DALAM FONOLOGI BAHASA JEPANG: ANALISIS POLA BUNYI DALAM KONTEKS PENGGUNAAN SEHARI-HARI - Azzahro, Nursyifa (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
The phenomenon of diphthong monophthongization is a phonological change that frequently occurs in everyday context and is worthy of further investigation. This qualitative descriptive study examined the phenomenon of diphthong monophongization in Japanese everyday usage. Employing the matching method and basic elemental sorting techniques, the study was analyzed using a generative transformation theory begun with the categorization of distinctive features. The objective of this study is to comprehend the alteration in the phonetic qualities of diphthongs [ei], [oɯ], and [ai] that undergo monophontongization in everyday language usage, as well as their positioning within syllables. The findings of the research indicated that diphthongs [ei] tend to monophontongize to [ee] exclusively at the end of syllables. In the contrast, the monophthongization of the diphthong [oɯ] occurs at the beginning, middle, and the end of syllables, whereas the monophtongization of the diphthong [ai] is complete and occurs only at the end of syllables.